Nefropatía asociada a infección por VIH en pacientes que reciben tratamiento antirretroviral en el Hospital Regional de Loreto, Iquitos - Perú 2016 - Gutiérrez Alvarado, Wilfredo Oswaldo (2021)
The prevalence of human immunodeficiency virus (HIV) tends to increase because antiretroviral treatment (ART) has managed to reduce morbidity and the transmission of the infection, with an increased risk of nephropathies. The objective of this study is to determinate nephropathy in patients with HIV-Infection who receive ART, being of the observational, analytical and retrospective cohort type. It was incorporated into the sample 61 patients, an instrument applied to the clinical records of the patients was used, and the data were subjected to a univariate and bivariate analysis. Results: The mean age of our patients was 42,08±11,27 years, 68,85% were males, 8,93% had arterial hypertension. Increased serum Creatinine (Cr) was 1,14mg/dL at the time of the study. The estimated glomerular filtration (eFG) calculated with the chronic renal disease epidemiology (CKD-EPI) collaborative equation decreased from 95,52 to 91,58 mL/min/1.73 m2. The prevalence of nephropathy in patients with HIV was 47,37% among the ages of 45 to 64, 42,11% in females, 20,00% in hypertensive patiens, 75,00% in obesos, 40,00% in those with <200 cél/mm3 of CD4, 50,00% in which they have viral load ? 100,002 copies/mL, 47,83% and 26,32% in which they received ABC, 3TC, EFV and AZT, 3TC, EFV respectively, 47,37% in those with proteinuria, 75,00% and 100,00% in those with high urea and creatinine serum. It is concluded that the prevalence of nephropathy was 39,34%. Routine nephrological evaluations should be incorporated including asymptomatic HIV patients, renal function tests such as microalbuminuria, glycosuria, phosphaturia and renal biopsy.